Dietary practices and nutritional status of primigravida women attending antenatal clinic at Embu level five hospital, Kenya - Ireri, Beatrice W.; Gitonga, Lucy K.; Kiboi, Willy K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Good nutrition during the antenatal period is vital for the well-being of the gravid woman and the developing fetus. There is limited data available regarding the dietary practices and nutrition status of pregnant women, specifically primigravida women. This study aimed at determining the dietary practices and nutrition status of primigravida women attending antenatal clinic at Embu Level Five Hospital, Kenya. Methods: The study adopted a cross-sectional analytical study design. All primigravida mothers aged between 18 and 49 years meeting the inclusion criteria were recruited for the study. Data was collected in the month of August 2023 using a researcher-administered semi-structured questionnaire. Association between dietary practices and nutrition status was established using regression analysis. Results: The majority 65.9%, (n=87) of the respondents had poor dietary practices while 70.5%, (n=93) of the participants were undernourished. The mean MUAC was SD 24.3±3.3 cm and the mean hemoglobin level was SD 12.04 ±1.6 g/dl. Those participants with good dietary practices were more likely to have good nutrition status compared to those with poor dietary practices (AOR = 1.61: 95% CI; 0.81–2.28). Conclusions: The study revealed a high burden of poor dietary practices and undernutrition among participants, with a positive trend between good dietary habits and better nutritional status. Nutrition education and behavior change interventions should be prioritised to improve dietary practices and overall nutritional health.